The effects of active and passive neck flexion on unilateral straight-leg-raising - Craig Smith (AOSIS, 1990)
A study was designed to test the effects of passive neck flexion (PNF) as compared with active neck flexion (ANF) on the straight-leg-raise (SLR) test. Twenty two subjects were measured three times with a goniometer and the difference in range of movement (ROM) was determined by subtracting the SLR recordings obtained by means of PNF from those of ANF. Results demonstrated that neck flexion (NF) performed actively allowed a mean value of 4,13° more SLR than when performed passively. The implications of these findings are discussed.